Industry-Oriented Career Guidance Model for Improving Employability of Vocational Education Students - Herianto; Aditia Gustiana Gunawan; Tuwoso; Hary Suswanto (Indonesian Scientific Publication, 2026)
Career guidance is widely seen as a key lever to help align vocational education with industry needs, but integrated and industry-driven career services are still commonly lacking. The study aims to investigate the impact of an industry-oriented career guidance model on improving vocational students’ employability and alignment with workforce needs. A Systematic Literature Review (SLR) following the PRISMA framework was conducted to analyze twenty peer-reviewed journal articles published between 2015 and 2026. The review focuses on identifying conceptual developments, implementation practices, and effectiveness factors related to industry-oriented career guidance. The review also highlights enabling factors, such as institutional support, career counsellor competencies, engagement with professional industries and students’ ability to adapt to careers. In addition, career guidance is an ecosystem-oriented process that acts as a link between curriculum development, the formation of professional identity, and portfolio readiness. Theoretically, this paper has highlighted the need to reposition career guidance as a strategic element of vocational education reform; and practically it has provided avenues for developing industry-responsive guidance systems.